Tama-risk? Avian responses to the invasion of saltcedars (Tamarix ramosissima) in Sonora, Mexico - Ian MacGregor-Fors; Rubén Ortega-Álvarez; Alfredo Barrera-Guzmán; Lucero Sevillano; Ek del del Val de Gortari (Revista Mexicana de Biodiversidad)
Although exotic plant invasions are one of the most important components of global change, previous studies have found some of the alien species to provide resources and/or conditions to native biota. One example of this is the saltcedar (Tamarix ramosissima). This exotic invasive tree has been related to several dramatic environmental changes in North America. However, previous studies suggest that they offer resources and conditions for native biota, such as the threatened southwestern willow flycatcher (Empidonax traillii). In this study, we surveyed avian communities and bird nests at sites severely invaded by saltcedars, moderately invaded sites, and non-invaded sites in northwestern Mexico. Our results show that although bird species richness and abundances do not differ among the studied conditions, species composition did. Also, bird nest density differed among the studied conditions, with non-invaded sites having the highest functional diversity of nesting birds. We suggest that future studies should gather natural history and ecological information that allows managing this invasive species correctly both in the USA and Mexico.